2000
DOI: 10.1034/j.1600-0706.2000.900313.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidden diversity and productivity patterns in mixed Mediterranean grasslands

Abstract: A detailed study of the variation in productivity across a diversity gradient in an experimental Mediterranean grassland examines the effects of a dominant perennial grass species upon the overall diversity–productivity relationship. The experiment took place at the Greek site of the European‐wide BIODEPTH programme. The experimental design is characterized by the use of a number of communities containing annuals and perennials within the total set of manipulated plots. The main results are: 1) a log‐linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 30 publications
10
40
0
Order By: Relevance
“…Originally, it was also presumed that selection effects would grow stronger through time as the most productive species came to dominance in polyculture (16). However, the fact that selection effects are often negative led some to argue that, as the least productive species come to dominate a community through time, complementarity must grow disproportionately strong to generate transgressive overyielding (22,24,30,31,43,44). Our analyses confirm that complementarity tends to increase through time, but they do not support the idea that selection effects change through time.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, it was also presumed that selection effects would grow stronger through time as the most productive species came to dominance in polyculture (16). However, the fact that selection effects are often negative led some to argue that, as the least productive species come to dominate a community through time, complementarity must grow disproportionately strong to generate transgressive overyielding (22,24,30,31,43,44). Our analyses confirm that complementarity tends to increase through time, but they do not support the idea that selection effects change through time.…”
Section: Discussionmentioning
confidence: 99%
“…Although, as we acknowledged in our report, our biomass patterns were partly generated by the effects of random sampling of species (1,22,23), wide reporting of other biodiversity function studies suggests that it is not appropriate to dismiss sampling effects as "artifacts" (24 -30). Rather, sampling effects can be considered results of random assembly or disassembly arising from the combination of probabilistic processes inherently associated with numerical components of diversity, differences in the biological traits of species, and ecological mechanisms that change abundances.…”
mentioning
confidence: 94%
“…In some cases certain sites were unusual, e.g., Portugal experienced a strong external effect from a dry period and particularly frosty winter. Greece showed no or little effect of diversity on aboveground biomass production (see also Troumbis et al 2000) and on most of the measured ecosystem processes, except for cotton decomposition where it showed the strongest effect of species richness. The fact that diversity had no effect on biomass at our least productive site (Greece) and increased with aboveground production, is consistent with Fridley (2002Fridley ( , 2003, who found that effects of experimental diversity gradients on productivity significantly increased with soil fertility (but see Kenkel et al 2000).…”
Section: Variation Of Diversity Effects With Sitementioning
confidence: 99%
“…The increase in cotton decomposition with greater diversity was clearly mainly driven by a strong relationship only at the Greek site. This is a good example of different processes responding differently to changes in diversity, since in Greece, where plants grew on an unusual soil high in Mg 2ϩ , Ca 2ϩ and very low in PO 4 3Ϫ (see Supplement), aboveground production and many other processes were largely unaffected (Troumbis et al 2000). In general, direct plant-diversity effects on processes such as wood decomposition would imply niche differentiation between plant species influencing this particular process (Lawton 2000).…”
Section: Linking Diversity Effects To Different Ecosystem Processesmentioning
confidence: 99%
See 1 more Smart Citation